The main stages of management accounting - Giyosov Ilhom Karimovich (International Consortium of Education and Culture Research Studies, 2019)
In the conditions of globalization of the world economy, it is important to establish an effective system of management accounting at the enterprise. Management system requires efficient management of material, financial and human resources and a complete analysis of economic activities when applying management accounting.